Taṭbīq Ṭarīqah at-Ta`allum at-Ta`āwunī Bi Uslūb JIGSAW Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Fahm an-Nuṣūṣ al-`Arabiyyah (Dirāsah Ijrāiyyah Bi Ma`had SMPIT Madrasah al-Qurān Aceh Besar): (Aceh Besar مدرسة القرآن SMPIT لترقية قدرة الطلبة على فهم النصوص العربية (دراسة إجرائية بمعهد JIGSAW تطبيق طريقة التعلم التعاوني بأسلوب - Aulia Agustiar; Nur Chalis (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
Students at SMPIT Madrasatul Quran boarding school memorize verses of al-Quran, memorize Arabic vocabulary, learn Arabic grammar, and learn Arabic texts. This process will be a good attempt to improve students' ability to read and understand Arabic texts. In reality, however, some students are not able to read and understand Arabic texts well, as there are errors in "Makhrajul Huruf", errors in "late rendering", errors in "stop places while reading texts" and are unable to "explain the meaning of the text read". Therefore, the researcher wanted to study the application of the cooperative learning method with the Jigsaw model to improve the ability of SMPIT Madrasatul Quran boarding school students to understand Arabic texts. The purpose of this study is to know the process of teaching students, and students' responses to learning and to know the efforts of teachers in applying cooperative learning methods with the Jigsaw model to improve the ability of SMPIT Madrasatul Quran boarding school students to understand Arabic texts. The approach of this research is a procedural research method. The research results that the cooperative learning method Jigsaw model is effective in improving the ability of SMPIT Madrasatul Quran boarding school students to understand Arabic texts as proof that the value of students in the first round is 66.89 (accepted). In the second half was 72.58 (acceptable). In the third round was 82.58 (good). In the fourth round, their value increased to 86.20 (good). Also after observing learning by using the cooperative learning method, there is a change in the teaching and learning process. The efforts of researchers in finding solutions to student problems have increased their competence and courage to read and understand Arabic texts.